Tweets and the streets : social media and contemporary activism - Gerbaudo, Paolo (Free online access: Knowledge Unlatched., 2012)
"From the Arab Spring to the 'indignados' protests in Spain and the Occupy movement, Paolo Gerbaudo examines the relationship between the rise of social media and the emergence of a new protest culture. Gerbaudo argues that activists' use of Twitter and Facebook does not fit with the image of a 'cyberspace' detached from physical reality. Instead, social media has been chiefly used as part of a project of re-appropriation of public space, and as a means to exert a form of soft leadership, involved in the 'choreographing' of collective action around symbolic 'occupied squares' from Tahrir to Zuccotti Park. Offering an exciting and invigorating journey through the politics of popular protest, this book points to both the possibilities and the risks that social media bring to the contemporary protest experience."--Page 4 of cover